Research on Semantic Based NGN Converged Service Composition Algorithm - Rongqun Peng; Lianjun Zhang; Zhengkun Mi (Dianxin kexue)
Analyzing the disadvantage of the two existing propylene-based service composition algorithms used in the converged process between telecommunication services and web services, a novel semantic-based double-chaining automatic composition algorithm was presented. Also, a distinct virtue in less time cost and higher composition success rate of the proposed algorithm than that of these existing related algorithms was proved by discussing its performance in detail. Additionally, a composing scenario of converged service was given to support the proposed DCA algorithm.